Molecular Hydrogen as an Emerging Therapeutic Medical Gas for Neurodegenerative and Other Diseases. (8th June 2012) - Ohno, Kinji; Ito, Mikako; Ichihara, Masatoshi; Ito, Masafumi
Abstract : Effects of molecular hydrogen on various diseases have been documented for 63 disease models and human diseases in the past four and a half years. Most studies have been performed on rodents including two models of Parkinson's disease and three models of Alzheimer's disease. Prominent effects are observed especially in oxidative stress-mediated diseases including neonatal cerebral hypoxia; Parkinson's disease; ischemia/reperfusion of spinal cord, heart, lung, liver, kidney, and intestine; transplantation of lung, heart, kidney, and intestine. Six human diseases have been studied to date: diabetes mellitus type 2, metabolic syndrome, hemodialysis, inflammatory and mitochondrial myopathies, brain stem infarction, and radiation-induced adverse effects. Two enigmas, however, remain to be solved. First, no dose-response effect is observed. Rodents and humans are able to take a small amount of hydrogen by drinking hydrogen-rich water, but marked effects are observed. Second, intestinal bacteria in humans and rodents produce a large amount of hydrogen, but an addition of a small amount of hydrogen exhibits marked effects. Further studies are required to elucidate molecular bases of prominent hydrogen effects and to determine the optimal frequency, amount, and method of hydrogen administration for each human disease.